Increased urinary B2-microglobulin is associated with poor prognosis of upper tract urothelial carcinoma - Han, Jang Hee; Jeong, Seung-hwan; Kim, Si Hyun; Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon (Frontiers in Oncology, 2022)
Background: Kidney tubular damage markers are biomarkers of acute or chronic kidney injury. Hypothetically, upper tract urothelial cancer (UTUC), which induces obstructive uropathy or direct invasion of the renal parenchyma, may also induce increased excretion of urinary tubular damage proteins. Therefore, this study aimed to investigate the use of tubular damage biomarker as prognostic markers for UTUC. Methods: The records of 417 surgically resected patients with UTUC were obtained from the Seoul National University Prospectively Enrolled Registry for urothelial cancer-upper tract urothelial cancer (SUPER-UC-UTUC) between January 2016 and December 2020. Patients with non-urothelial cancer or without urinary tubular injury marker measurement were excluded, and finally, 296 patients were finally included. B2-microglobulin (B2-MG) was an injury marker, and a value higher than 0.3 was considered abnormally elevated, according to previous studies. Results: The mean age was 70.9 years, and the male sex was predominant (n = 211, 71.3%). The incidences of renal pelvis and ureter cancer were similar (50.7% vs. 49.3%). Most patients had high-grade diseases (n = 254, 88.8%). The high urine B2-MG group was older, had decreased renal function, and had a higher pathologic T stage than did the low group. Multivariate Cox regression analysis of disease-free survival (DFS), open surgical method (Hazard ratio (HR) 1.52, p = 0.027), large tumor size (HR 1.06, p = 0.017), tumor multifocality (HR 1.90, p = 0.038), lymphovascular invasion (HR 2.19, p < 0.001), and high urine B2-MG (HR 1.57, p = 0.021) were significantly associated with shortened metastasis-free survival (MFS). Kaplan–Meier curve analysis revealed short DFS (median survival 15.5 months vs. unattained, log-rank p = 0.001) and MFS (unattained median survival in both groups, log-rank p = 0.003) for the high urine B2-MG group compared to the low urine B2-MG group. Conclusion: Patients with UTUC presenting with increased pre-operative urine B2-MG levels were associated with disease recurrence and metastasis. This biomarker may aid in performing pre-operative risk stratification and in assessing the individual prognosis of patients with UTUC.